2023
DOI: 10.31026/j.eng.2023.02.10
|View full text |Cite
|
Sign up to set email alerts
|

Applying the WaterGEMS Software to Conduct a Comparison of the Darcy-Weisbach and Hazen-Williams Equations for Calculating the Frictional Head Loss in a Selected Pipe Network

Abstract: Darcy-Weisbach (D-W) is a typical resistance equation in pressured flow; however, some academics and engineers prefer Hazen-Williams (H-W) for assessing water distribution networks. The main difference is that the (D-W) friction factor changes with the Reynolds number, while the (H-W) coefficient is a constant value for a certain material. This study uses WaterGEMS CONNECT Edition update 1 to find an empirical relation between the (H-W) and (H-W) equations for two 400 mm and 500 mm pipe systems. The hydraulic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Efficient water distribution and supply are of predominant vital in the engineering design and operation of new and existing water supply and water distribution networks or the flourishing of the existing water supply and distribution scheme (Sreemathy et al, 2017). In the case of the water treatment and processing industry, pipeline troubles bring grievous consequences, inducing traffic fatal accidents and death, flooding, financial, time and materials losses and the break of the water distribution supply (Abdulsamad and Abdulrazzaq, 2023;Hamad et al, 2023). Various factors govern the selection of materials for pipe networks and pipelines.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Efficient water distribution and supply are of predominant vital in the engineering design and operation of new and existing water supply and water distribution networks or the flourishing of the existing water supply and distribution scheme (Sreemathy et al, 2017). In the case of the water treatment and processing industry, pipeline troubles bring grievous consequences, inducing traffic fatal accidents and death, flooding, financial, time and materials losses and the break of the water distribution supply (Abdulsamad and Abdulrazzaq, 2023;Hamad et al, 2023). Various factors govern the selection of materials for pipe networks and pipelines.…”
Section: Introductionmentioning
confidence: 99%
“…Where; Re is equivalent to Reynolds number (dimensionless); α is equivalent to the density of the fluid or average discharge density (kgm -3 ); δ is equivalent to average discharge or discharge rate (m 3 s -1 ); d is equivalent to length index or pipe diameter (mm or m); γ is equivalent to a dynamic viscosity of the fluid (kgms -1 ); λ is equivalent to wall roughness of the individual pipe (mm or m). More studies on head loss computation, water supply and distribution and pipe network analysis can be established in the previous studies such as Nielsen (1989); Swamee and Sharma (2008) 2023) and Abdulsamad and Abdulrazzaq (2023). These previous studies have reported and documented several computer programs which can easily be used on personal laptops and computers to easy pipe network analysis, water distribution design and pipeline design.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation